Size differences of Arctic marine protists between two climate periods—using the paleoecological record to assess the importance of within‐species trait variation. Issue 1 (27th November 2016) - Mousing, Erik A.; Ribeiro, Sofia; Chisholm, Chelsea; Kuijpers, Antoon; Moros, Matthias; Ellegaard, Marianne
Abstract: Mean body size decreases with increasing temperature in a variety of organisms. This size–temperature relationship has generally been tested through space but rarely through time. We analyzed the sedimentary archive of dinoflagellate cysts in a sediment record taken from the West Greenland shelf and show that mean cell size decreased at both intra‐ and interspecific scales in a period of relatively warm temperatures, compared with a period of relatively cold temperatures. We further show that intraspecific changes accounted for more than 70% of the change in community mean size, whereas shifts in species composition only accounted for about 30% of the observed change. Literature values on size ranges and midpoints for individual taxa were in several cases not representative for the measured sizes, although changes in community mean size, calculated from literature values, did capture the direction of change. While the results show that intraspecific variation is necessary to accurately estimate the magnitude of change in protist community mean size, it may be possible to investigate general patterns, that is relative size differences, using interspecific‐level estimates. Abstract : Changes in protist size and community mean size are related to temperature changes through time by measuring dinoflagellate cysts in two contrasting temperature periods in a sediment core collected in Disko Bay, Greenland. We show that protist were smaller at both intra‐ and interspecific scales in the warm period compared with the cold period and that intraspecific variation accounted for 70% of the change at the community level. We compare our results to size estimates in the literature and show that while interspecific‐scale estimations can be used to investigate general patterns, for example, relative changes in size, intraspecific variation is necessary to accurately estimate the magnitude of change.